2016
DOI: 10.1038/ncomms13187
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-activated protein kinase G Iα regulates cardiac diastolic relaxation and fine-tunes the Frank–Starling response

Abstract: The Frank–Starling mechanism allows the amount of blood entering the heart from the veins to be precisely matched with the amount pumped out to the arterial circulation. As the heart fills with blood during diastole, the myocardium is stretched and oxidants are produced. Here we show that protein kinase G Iα (PKGIα) is oxidant-activated during stretch and this form of the kinase selectively phosphorylates cardiac phospholamban Ser16—a site important for diastolic relaxation. We find that hearts of Cys42Ser PKG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Although it failed to reach significance, this is in line with the previously published data for younger mice [8] , [12] . KI mice fed a normal diet had smaller left ventricular diastolic dimension and volume than the WT mice on a normal diet, consistent with the diastolic dysfunction observed in the KI mice previously [8] , [10] . The obesogenic high fat diet caused both systolic and diastolic dysfunction in the WT mice ( Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Although it failed to reach significance, this is in line with the previously published data for younger mice [8] , [12] . KI mice fed a normal diet had smaller left ventricular diastolic dimension and volume than the WT mice on a normal diet, consistent with the diastolic dysfunction observed in the KI mice previously [8] , [10] . The obesogenic high fat diet caused both systolic and diastolic dysfunction in the WT mice ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…Protein kinase G (PKG) is the end-effector kinase that mediates nitric oxide (NO)-dependent vasorelaxation [7] , with the Iα isoform mediating oxidant-dependent vasorelaxation to maintain normal healthy blood pressure [8] , [9] and regulate diastolic relaxation [10] . Whilst these finding support a role for oxidant-activated PKG Iα in the maintenance of health, oxidation of this kinase have also been observed in the pathogenesis of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, oxidation of Cys42 may not induce substantive catalytic activation compared to cGMP-dependent activation of the kinase 25 . Given that Cys42 is localised in the N-terminal leucine zipper domain that is important for substrate targeting 26 , the redox state of this thiol may be more important for modulating such interactions, as suggested previously 27 29 . Consistent with this regulatory role, Cys42Ser PKGIα knock-in (KI) mice, which cannot form the interprotein disulfide, are hypertensive 30 , illustrating a physiological role for oxidants in blood pressure regulation.…”
Section: Introductionmentioning
confidence: 77%
“…Ion channels regulate cardiac excitability and contractility with millisecond timescales, raising the possibility that thiol-reactive NO species modulate heart function via protein S-nitrosation on a beat-to beat basis [74]. Recently we reported that disulfide formation in myocardial protein kinase G I rapidly regulates diastolic relaxation [75], consistent with this oxidative modification also being capable of regulation with a millisecond timescale. Whilst both these are possibilities are interesting, the half-life of these modifications has yet to be determined.…”
Section: Further Considerations Of the Stability Of Protein S-nitrosomentioning
confidence: 89%